BEAVERS: skilful dam constructors - YAHYA, HARUN (GOODWORD BOOKS New Dehli, 2022)
"Beavers: Skilful Dam Constructors" is an informative book that explores the fascinating world of beavers and their remarkable ability to construct intricate dams. The text delves into the biology and behavior of these industrious animals, highlighting their natural instincts and engineering skills that allow them to manipulate their environment. Through engaging illustrations and detailed explanations, the book covers the ecological impact of beaver dams on local ecosystems, including their role in creating wetlands and supporting biodiversity. This work aims to educate readers about the importance of beavers in nature and the need to conserve their habitats.